2020
DOI: 10.1007/s43390-019-00018-y
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic mobility and its relation to pulmonary function and rib-cage deformity in patients with early onset idiopathic scoliosis: a long-term follow-up

Abstract: Study design A group of adult patients with idiopathic scoliosis, diagnosed before the age of ten, at a mean of 26.5 years after treatment with either brace or surgery during childhood and adolescence attended a clinical follow-up. Objectives To evaluate the relation between thoracic mobility, rib-cage deformity, and pulmonary function. Summary of background data Long-term studies of pulmonary function in relation to thoracic mobility after treatment in this patient group have not been published. Methods A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…For this reason, this study was limited to male participants. In addition, healthy young participants were included because reduced thoracic mobility is influenced by disease and aging ( Moll and Wright, 1972 ; Rehman et al, 2020 ; Romberg et al, 2020 ), and skeletal muscle stiffness varies with age ( Hirata et al, 2020 ; Kelly et al, 1993 ). Therefore, the results may differ in women, patients, and the elderly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, this study was limited to male participants. In addition, healthy young participants were included because reduced thoracic mobility is influenced by disease and aging ( Moll and Wright, 1972 ; Rehman et al, 2020 ; Romberg et al, 2020 ), and skeletal muscle stiffness varies with age ( Hirata et al, 2020 ; Kelly et al, 1993 ). Therefore, the results may differ in women, patients, and the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…The thorax is composed of the thoracic vertebrae, ribs, and sternum and has the mobility to expand its antero-posterior and lateral diameters with inspiration during respiration ( Moll and Wright, 1972 ). Thoracic mobility has been reported to be reduced in respiratory diseases such as chronic obstructive pulmonary disease ( Reddy et al, 2019 ), ankylosing spondylitis (AS) ( Hsieh et al, 2016 ), and scoliosis ( Romberg et al, 2020 ). Hsieh et al (2016) showed that AS patients with reduced thoracic mobility had reduced lung capacity compared with healthy participants.…”
Section: Introductionmentioning
confidence: 99%
“…Reduction of thorax expansion may compromise the volume of the chest, with 20% loss of its normal capacity ( 6 ). The type of prosthesis is also critical because most of the patches are non-absorbable and synthetic and the patients are often young, with a long-life expectancy ( 10 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…The larger the movement of the ribs, the larger the change in thoracic volume. Therefore, greater changes in gas pressure inside the thorax will lead to larger amounts of gas being exchanged to achieve pulmonary ventilation [ 5 , 6 ]. Therefore, once rib fractures happen, it will cause some degree of decline in pulmonary ventilation function.…”
Section: Introductionmentioning
confidence: 99%